Validation of a hypomorphic variant in CDK13 as the cause of CHDFIDD with autosomal recessive inheritance through determination of an episignature - Jan Fischer; Mariëlle Alders; Marcel M. A. M. Mannens; David Genevieve; Karl Hackmann; Evelin Schröck; Bekim Sadikovic; Joseph Porrmann (Clinical Epigenetics)
Abstract Autosomal dominant CDK13-related disease is characterized by congenital heart defects, dysmorphic facial features, and intellectual developmental disorder (CHDFIDD). Heterozygous pathogenic variants, particularly missense variants in the kinase domain, have previously been described as disease causing. Using the determination of a methylation pattern and comparison with an established episignature, we reveal the first hypomorphic variant in the kinase domain of CDK13, leading to a never before described autosomal recessive form of CHDFIDD in a boy with characteristic features. This highlights the utility of episignatures in variant interpretation, as well as a potential novel diagnostic approach in unsolved cases or for disease prognosis.